Modern advanced accounting / Egyptian Edition - Larsen, E. John.; Eldeeb, Mohamed Samy; Tarek Abdel Fattah (McGraw-Hill/Irwin, London, 2013)
The emphasis throughout this highly-regarded advanced accounting text is on financial accounting concepts and their application in business. Partnerships, affiliated companies, and topics such as international accounting standards and business segments are covered with clear and up-to-date presentations as well as added coverage of the Egyptian Accounting Standards and business context. In addition, this text continues to include case studies that integrate the coverage of ethics in accounting as well as encourage analytical and conceptual thinking.
Keywords: Accounting